Improvement of anticorrosive performance of phosphate-based alkyd paints with suitable additives - Blustein, Guillermo (2011)
The purpose of this investigation was focused on reducing the content of zinc phosphate in anticorrosive paints by means of the incorporation of low quantities of selected soluble corrosion inhibitors. The article describes the anticorrosive behavior of alkyd paints containing reduced levels of zinc phosphate, zinc oxide, and some soluble compounds used as additives (e.g., sodium polyphosphate, sodium phosphate, and sodium benzoate). Anticorrosive solventborne alkyd paints were formulated with a zinc phosphate content of 10% by volume (v/v) with respect to the total pigment concentration. In all cases, the PVC/CPVC (pigment volume concentration/critical pigment volume concentration) ratio was 0.8. Experimental paints, applied on sandblasted SAE 1010 panels, were evaluated by accelerated tests (salt spray cabinet) and electrochemical measurements (electrochemical impedance spectroscopy, EIS). The results show that the additions of small amounts of soluble corrosion inhibitors to low content zinc phosphate paint formulations enhance their performance in a very remarkable way. Perhaps, the most outstanding feature is that the employment of soluble additives allowed the reduction of the zinc phosphate content with concomitant savings.